Distribuiç\~ao territorial dos desembolsos do BNDES para a indústria e a infraestrutura entre 2000 e 2018 - Raphael de Oliveira Silva; Mabel Diz Marques (Instituto de Pesquisa Econômica Aplicada (IPEA), 2021)
– This study aims to investigate the patterns and patterns of distribution of funds from the National Bank for Economic and Social Development (BNDES) on industry and infrastructure, with emphasis on the sectorial and regional vectors of its performance in Brazil. The approach is based on the use of analytical, descriptive and statistical methods and based on data that are registered by the BNDES and the Annual List of Social Information (RAIS) for the period 2000-2018. The results suggested for the BNDES in the most recent period, expanded the financing of the Brazilian industry and infrastructure in all macro-regions, demonstrating, even on a modest scale, a process of deconcentration. As more consolidated industrial agglomerations, they still retain great relevance in the absorption of resources (both for industry and infrastructure) and are located, mainly, in the proximity of the main capitals and coastal strip. However, the results are evident when the BNDES carries out actions of smaller size agglomerations, mainly those belonging to regions targeted by the regional policy (North, Northeast and Midwest), a process that can be considered in the edition of new local productive arrangements.
Keywords: R11; G32; L50; O20; 330; BNDES; financing; transformation industry; infrastructure; regional development